Evaluating the effect of a virtual reality digital therapeutic on maternal stress among expectant and postpartum Black and Latina mothers: a protocol paper - Carrasco, Mary; Dimanche, Stacyca; Fouladian, Joshua; Neff, Marisela; Scaramutti, Carolina; Moloney, Mairead; Blanc, Judite; Seixas, Azizi (Frontiers in Psychiatry, 2024)
BackgroundMaternal mental health is vital to overall well-being, particularly among expectant and postpartum Black and Latina women who experience higher stress levels and mental health challenges. Traditional healthcare systems often fail to meet these needs, underscoring the need for innovative and accessible interventions. NurtureVR, a digital maternal mental health and educational program, leverages virtual reality to offer mindfulness, relaxation, and guided imagery to support these women.ObjectivesThis protocol aims to evaluate whether NurtureVR, a digital therapeutic, can reduce stress levels and mental health symptoms in pregnant and postpartum Black and Latina women, improve sleep, enhance pregnancy and childbirth experiences, and increase pregnancy and postpartum health literacy.MethodsThe Nurturing Moms study uses a pre- and post-intervention design with a 5-week NurtureVR program. Fifty participants, 25 expectant and 25 postpartum Black and Latina women, will be recruited through clinics, community organizations, and online platforms. The study involves three phases: baseline assessments of stress, mood, self-efficacy, demographics, and health history; daily use of NurtureVR for 15 minutes during the third trimester and six weeks postpartum; and follow-up assessments at six weeks postpartum. The program includes 49 modules on labor and delivery, stress during pregnancy, nutrition, breastfeeding, hormonal changes, 3D VR representations of fetal development, pain management simulations, and mindfulness exercises for labor. Participants will report stress, anxiety, mood, and pain levels following each VR session. Additional qualitative insights will be gathered through focus groups, and an optional survey will be administered one-year post-intervention to evaluate long-term effects.ConclusionsThe Nurturing Moms study seeks to create a more inclusive and equitable healthcare landscape, demonstrating that digital interventions like NurtureVR are essential for providing high-quality maternal care. By democratizing access to clinical research and healthcare, this decentralized trial promotes equity, improves the generalizability of findings, and accelerates the development of new treatments. The study’s innovative approach has the potential to improve maternal experiences of stress, sleep, and overall health outcomes for Black and Latina mothers and children, despite limitations such as sample size, language barriers, and the preliminary nature of a pilot and feasibility study.